ψ(3770) resonance and its production in p¯p→DD¯ - Haidenbauer, J.; Krein, G. [UNESP] (Amer Physical Soc, 2015)
The production of a D (D) over bar meson pair in antiproton-proton ((p) over barp) annihilation close to the production threshold is investigated, with special emphasis on the role played by the psi(3770) resonance. The study is performed in a meson-baryon model where the elementary charm production process is described by baryon exchange. Effects of the interactions in the initial and final states are taken into account rigorously, where the latter involves also those due to the psi(3770). The predictions for the D (D) over bar production cross section are in the range of 30-250 nb, and the contribution from the psi(3770) resonance itself amounts to roughly 20-80 nb.